Relationship between teaching and learning approaches and student engagement at a selected Malaysian Research University - Teoh, Hee Chong (2015)
Student Engagement is significantly associated with the personal development of undergraduates, as well as the institutional development of tertiary education. The scenario of disengagement will affect students‟ performance during their collegiate life and their career advancement after they graduate. Therefore, this study investigates Approaches to Teaching and Student Approaches to Learning of university students towards predicting Student Engagement and Academic Achievement in their university experience. In addition, this study explores the level of Student Engagement, Academic Achievement, Approaches to Teaching and Student Approaches to Learning among undergraduates. A correlational research design was used in this study. The respondents comprised 350 second year students from a local public university. The data for this study were collected by utilizing three instruments, namely Student‟s Perception on Approaches to Teaching Inventory (to measure the Approaches to Teaching), Study Process Questionnaire – 2 Factors (Malaysia) (to measure Student Approaches to Learning) and Student Engagement Questionnaire (to measure Student Engagement). Data were analysed using descriptive and inferential statistics. The study found that the majority of students demonstrated a moderate level of engagement in their university experience. Among the five constructs of Student Engagement, students showed a high level of Life-long Learning interest, followed by a moderate level of Cooperative Learning, Active Learning, Student-faculty Interaction and Experience with Diversity. The findings of this study did not show any significant difference for the engagement level of male and female students, or in respect of the five constructs of Student Engagement. The findings also revealed that students possessed a high level of Academic Achievement in their study. Students in this study perceived that their lecturers applied a moderate level of Teacher-focused teaching approach. Meanwhile, students perceived their lecturers applied a high level of Student-focused teaching approach. This study further identified that students adopted a moderate level of Surface and Deep Approaches in their study. All the variables involved in this study were found to have significant correlation with each other. The results of path analysis confirmed the fit of the proposed Teaching and Learning Engagement model. This model was also suitable for use with male and female students. The model indicated that the Teacher-focused teaching approach has a significant direct effect on the Surface Approach and Academic Achievement. The student-focused teaching approach was also found to have a significant direct effect on the Surface Approach, Deep Approach and Student Engagement. In addition, the Deep Approach was also found to have a significant effect on Student Engagement. The Deep Approach also partially mediated the relationship between the Student-focused teaching approach and Student Engagement. No significant differences were found for the direct and indirect effects among variables across gender. In conclusion, this study found that the proposed Teaching and Learning Engagement model fitted the sample data well. The data analysis also found that Approaches to Teaching (Student-focused and Teacher-focused) and Student Approaches to Learning (Deep and Surface Approaches) had a different degree of direct and indirect effects on Student Engagement and Academic Achievement.